Antithrombin attenuates the progression of hepatocellular carcinoma by regulating neutrophil/interleukin‐8 signaling. Issue 11 (7th September 2020) - Okimoto, Sho; Tashiro, Hirotaka; Iwako, Hiroshi; Kuroda, Shintaro; Kobayashi, Tsuyoshi; Hinoi, Takao; Ohdan, Hideki
Abstract : Aim: Inflammation plays an important role in hepatocellular carcinoma (HCC) progression. Here, we examined whether antithrombin (AT) plays a role in attenuating HCC progression, via its anti‐inflammatory effects. Methods: HCCs were developed in AT‐insufficient (AT +/− ) mice and wild‐type (AT +/+ ) mice treated with diethyl nitrosamine and carbon tetrachloride. AT was administered to AT +/− mice. The development of HCC was compared between the three groups. In vitro study, migration assay was performed. The association of the prognosis of patients with HCC and plasma AT values was clinically examined. Results: AT suppressed the release of interleukin (IL)‐8 from lipopolysaccharide (LPS)‐stimulated human neutrophils in vitro . Huh‐7 cells that were co‐cultured with neutrophils and stimulated with LPS showed significantly enhanced migration; however, Huh‐7 cells co‐cultured with LPS/AT‐stimulated neutrophils showed significantly decreased migration. Moreover, the addition of anti‐IL‐8 antibodies to LPS‐stimulated Huh‐7 cells co‐cultured with neutrophils also suppressed migration. AT +/− mice (AT plasma activity: 64%) promoted liver cancer, as compared with wild‐type mice (AT plasma activity: 135%); AT administration attenuated liver cancer in AT +/− mice. Patients with HCC with a preoperative AT level of ≥70% showed better outcomes after liver resection, as compared with those with an AT level of <70%. IL‐8 expression and neutrophil infiltration in HCC tissues were negatively correlated with the AT level. Conclusions: AT attenuates HCC progression by regulating neutrophil/IL‐8 signaling.